The Effect of Education Using Video Media on Mothers' Knowledge About Giving MP-ASI to Babies Aged 6-12 Months - Kaimarehe, Yolanda (Jurusan Kebidanan Poltekkes Kemenkes Sorong, 2024)
The problem of malnutrition in toddlers is the impact of the lack of exclusive breastfeeding for up to 6 months. The aim of this research is to determine the effect of video media on mothers' knowledge about giving MP-ASI to babies aged 6-12 months at the Roswar Community Health Center. The type of research is quasi experimental research, namely research that tests interventions on a group of subjects, with a research design using a one group pre test-post test design. This research was carried out by providing video media with a frequency of giving once with a duration of 5-10 minutes, then the data will be analyzed using a non-parametric test using the Wilcoxon test. The research results showed that the average value of maternal knowledge increased after being given video media intervention and based on the results of statistical tests it was found that the p-value of maternal knowledge before and after treatment was 0.00. The conclusion is that there is a difference in mothers' knowledge about giving MP-ASI to babies aged 6-12 months before and after being given video media at the Roswar Community Health Center.